Model Pendidikan Agraria Berbasis Budaya Lokal dan Kesadaran Historis di SMK Pasawahan Banjarsari - Soni Ramdani; Irvan Badrul Jaman; Fahlan Munparidz; Pani Silviani (Universitas Galuh, 2025)
The study aims to analyze the model of agrarian education based on local culture and historical awareness at SMK Pasawahan Banjarsari. The study uses a qualitative approach with a case study design. The informants consist of the principal, teachers, students, and alumni. Data were collected through semi-structured interviews, observations, and documentation studies. Data analysis was conducted using thematic analysis with the stages of coding, categorization, and meaning extraction. The results of the study indicate that the integration of agricultural practice learning with agrarian history and local culture shapes students' technical competencies while strengthening historical awareness, work character, and entrepreneurial orientation. This study contributes to the development of the concept of community-based vocational education for farmers that links learning experiences with agrarian identity and social sustainability.